An Assessment of the Immigration Impact on the International Housing Price - Teodora Cristina Barbu; Mariana Vuță; Adina Ionela Străchinaru; Sorin Iulian Cioacă (Amfiteatru Economic Journal, 2017)
The article highlights the correlation between the evolution of the housing price, as measured by House Price Index, the flow of immigrants and other macroeconomic variables for a sample of 21 representative countries for the period 2007-2014. The proposed model explains and highlights the existence of a positive link between the House Price Index evolution and the flow of immigrants , market capitalization share to Gross Domestic Product and the growth rate of the economy. The novelty of this study is derived from the use of panel data models, the results indicating that for one percent increase in immigration (measured by the flow of immigrants), the housing price changes, in the same way, by 0.045%. It confirms the existence of a positive link, although not significant to the level of the housing price. The article is divided into four parts: the first part explains the choice of this topic; the second part presents an overview of the main ideas that are found in the literature; the third part presents the methodology and models applied to identify the immigration impact on the housing price and the fourth part contains conclusions, test limits and future research directions.
Keywords: F22; J11; 330; immigration; house price index (HPI); unemployment rate; capital market; economic growth